TINJAUAN YURIDIS TERHADAP BERAKHIRNYA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG TERHADAP PT.BUANA CHANDRA MANDIRI OLEH PT. GAJAH MAS MULIA: Judicial Review The End Of Posponement Debt Payments Obligations to PT. Buana Chandra Mandiri by PT.Gajah Mas Mulia - Raffee Denli Ramiro; Sri Bakti Yunari (AMICUS CURIAE, 2025)
A PKPU debtor is a debtor who delays debt repayment until able to settle matured obligations, has at least two creditors, and can be petitioned for PKPU by themselves or by a creditor. A concluded PKPU may lead to bankruptcy, as in the case of PT. Buana Chandra Mandiri under Supreme Court Decision Number 41K/Pdt.Sus-Pailit/2024 upon the petition of PT. Gajah Mas Mulia. This study employs a normative juridical and descriptive method using a qualitative approach. In this case, the end of PKPU caused PT. Buana Chandra Mandiri’s assets to be transferred as bankruptcy assets. Conversely, the PKPU petition by PT. Gajah Mas Mulia was rejected by the Surabaya Commercial Court due to insufficient assurance of repayment. The identified problem in this study is the inconsistency between the court’s decision and the provisions of the Bankruptcy and PKPU Law, particularly Articles 268, 280, 281, and 289, as the peace proposal was denied and the voting process failed to meet quorum. Based on the results and conclusion of the study, it is concluded that the judges’ ruling in this case contains legal errors and is considered an obscure libel, thus not in accordance with bankruptcy law principles.